Facilitating enzymatic reactions by using ionic liquids: a mini review - Elgharbawy, Amal A.M.; Moniruzzaman, Muhammad; Goto, Masahiro (Elsevier B.V., 2021)
Over the past two decades, ionic liquids (ILs) have been widely used for enzymatic conversions of substrates — especially substrates that are insoluble in common organic solvents and water — resulting in high conversion rates, high selectivity, and improved enzyme stability, wherein the ILs are recoverable and recyclable. Compared with performance in first-generation ILs, researchers recently considerably improved the technological utility of enzymes in second- and third-generation ILs composed of enzyme-benign cations and anions. Use of upgraded ILs with enzymes offers further improved activity and stability compared with research studies in the past decade, rendering IL-assisted biocatalytic processes more environmentally and economically attractive. This short review briefly presents recent developments of enzymatic reactions in ILs. The review covers approaches for and modifications of enzymes and ILs within the past 2 years for improved enzymes performance in ILs.